Rancang Bangun Aplikasi Bimbingan Skripsi Online Berbasis Android Dengan Metode Human Centered Design - Hidayat, Muh. Adrian Juniarta; Bahtiar, Hariman; Putra, Yupi Kuspandi; Fathurrahman, Fathurrahman (Jurnal Bumigora Information Technology (BITe), 2023)
Application-based services are currently increasingly being used, one of which is thesis guidance services for final year students. The process of completing students' final assignments is sometimes difficult to monitor due to the lack of time for supervisors and students to meet. In this research, it is proposed to create an online thesis guidance service system based on an Android application. In the application that will be built, all features will be tailored to the specific needs of users, namely the needs of supervisors and students in providing online thesis guidance services. Therefore, it is proposed to design applications using the Human Centered Design (HCD) method. HCD is a method of developing software that focuses on the needs of certain user groups by conducting needs analysis directly with potential users. By using this method, it was found that the application that was built functioned very well and met user expectations, where the level of user satisfaction with the features provided was very good.